Research on the correlation between component elements and psychological perception of the spatial form of underground commercial street corners based on virtual reality technology - Sun, Liang; Fang, Tianyu; Sun, Yan; Wang, Bo; Shao, Zebiao (Frontiers in Psychology, 2022)
The corner space, an important area of underground commercial streets, not only converts space functions but also exerts a great impact on the space atmosphere by transforming the environmental quality of the commercial street space. Based on corner space investigations of several underground commercial streets in China, this paper constructs a realistic scene model using virtual reality technology and screens, This paper classifies the corner space elements of underground commercial streets through preliminary experiments. Based on the conclusions, different morphological models of the corner space were constructed by orthogonal experiments and virtual reality technology combined with psychology. A semantic differential was used to quantitatively evaluate and analyze the spatial experience cognition of the subjects. This enabled an analysis of the of underground commercial street corners’ relationship to the component elements and the visitors’ psychological perception of their spatial form.